Mapping Research Themes on Sustainable Finance: A Scientometric Review from Scopus Database - Judijanto, Loso (West Science Business and Management, 2025)
This study presents a scientometric analysis of the global research landscape on sustainable finance using data retrieved from the Scopus database. By employing VOSviewer for bibliometric mapping, the study identifies major themes, influential authors, collaborative networks, and temporal trends within the literature published between 2000 and 2025. The analysis reveals that sustainable finance is anchored around core topics such as green finance, climate change, ESG performance, and responsible investment, while new themes like financial inclusion, digital finance, and greenwashing are gaining prominence. Keyword co-occurrence and overlay visualizations highlight the dynamic evolution of research interests, shifting from environmental and policy-centered discussions toward technologically driven and socially responsive financial practices. The study also maps institutional and country-level collaborations, identifying dominant players as well as regions with emerging contributions. This comprehensive overview provides valuable insights for researchers, policymakers, and financial practitioners seeking to understand the intellectual structure of sustainable finance and to identify strategic directions for future inquiry and action.